Amount of carbon fixed, transit time and fate of harvested wood products define the climate change mitigation potential of boreal forest management—A model analysis - Metzler, Holger; Launiainen, Samuli; Vico, Giulia (Elsevier, 2024)
Boreal forests are often managed to maximize wood production, but other goals, among which climate change mitigation, are increasingly important. Hence, it is necessary to examine synergies and trade-offs between forest production and its potential for carbon sequestration and climate change mitigation in forest stands. To this aim, we develop a novel mass-balanced process-based compartmental model that allows following the carbon path from its photosynthetic fixation until its return to the atmosphere by autotrophic or heterotrophic respiration, or by being burnt as wood product. Following carbon in the system allows to account for how long forest ecosystems and wood products retain carbon away from the atmosphere (i.e., the carbon transit time). As example, we apply the model to four management scenarios, i.e., mixed-aged pine, even-aged pine, even-aged spruce, and even-aged mixed forest, and contrast metrics of performance relative to wood production, carbon sequestration, and climate change mitigation potential. While at the end of an 80 yr rotation the even-aged forests held up to 31% more carbon than the mixed-aged forest, the mixed-aged forest was superior during almost the entire rotation when factoring in the carbon retention time away from the atmosphere, i.e., in terms of climate change mitigation potential. Importantly, scenarios that maximize production or amount of carbon stored in the ecosystems are not necessarily the most beneficial for carbon retention away from the atmosphere. These results underline the importance of considering carbon transit time when evaluating forest management options for potential climate change mitigation.
Keywords: boreal forest; wood production; carbon sequestration; transit time; climate change mitigation; process-based modeling